Research on tourism development of Xinjiang based on grey relational analysis and gravity model. Issue 3 (13th October 2014) - zhou, lei; Dong, QingMing; Liu, Sifeng; Xie, Naiming
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper attempts to apply grey correlation analysis method and gravity model to solve the research on Xinjiang tourism resources strategic development, which can be viewed as an important part of the problems of Xinjiang tourism economic development. Design/methodology/approach Starting from the fact that the unbalanced development of local tourism economy often appears in Xinjiang tourism economic development.On the basis of the theory of grey relational analysis of Ju-long Deng and the theory of gravity model of Smith D and Haggett P, this paper systematically utilizes the grey relational analysis to analyze the key factors affecting tourism economy in Xinjiang, and apply gravitational model to analysis tourism impact degree Between different areas in Xinjiang. Findings The results show that different areas of Xinjiang are in the oasis belt, the economic level is not balanced, effects of passenger volume and civilian vehicle number of tourism economy is relatively large. In addition, the study finds that the linking degree of regional tourism economic is non-equalizing. Practical implications Given the fact that the tourism economic development plays an important role in the economic development of Xinjiang, this paper applys gray correlation analysis and gravitational model to analyze factors affecting the development of tourism and the gap of tourism economy between different regions of Xinjiang. According to the analysis of the problems found, this paper proposes some reasonable suggestions on the development of Xinjiang tourism economy . Originality/value This paper succeeds in providing combination of gray correlation analysis and gravitational model to solve the question of tourism economy development in Xinjiang.